2020
DOI: 10.3389/fmicb.2020.558166
|View full text |Cite
|
Sign up to set email alerts
|

RskA Is a Dual Function Activator-Inhibitor That Controls SigK Activity Across Distinct Bacterial Genera

Abstract: It has been previously shown that RskA, the anti-Sigma factor K of Mycobacterium tuberculosis, inhibits SigK and that mutations in RskA promote high expression of the SigK regulon. The latter observation led us to hypothesize that RskA mutations lead to loss of the anti-Sigma factor function. In this report, we used natural and artificial mutations in RskA to determine the basis of the SigK-RskA partnership. Consistent with predictions, the N-terminal cytoplasmic portion of RskA was sufficient on its own to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…To investigate whether T cell differentiation and vaccine protection is directly linked to in vivo antigen transcription, we utilized a recently engineered H37Rv strain ( 36 ) (herein called H37Rv::mpt70 high ) with significantly increased in vitro expression of MPT70 due to insertion of sigK (Rv0445c) and rskA (Rv0444c) from Mycobacterium orygis ( 6 , 36 ). In line with the previous report ( 36 ), we observed that this strain upregulated in vitro expression of MPT70 compared to wild-type (WT) H37Rv, while very little change was observed for the regulators of MPT70 transcription (SigK and RskA) ( Fig. 4a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate whether T cell differentiation and vaccine protection is directly linked to in vivo antigen transcription, we utilized a recently engineered H37Rv strain ( 36 ) (herein called H37Rv::mpt70 high ) with significantly increased in vitro expression of MPT70 due to insertion of sigK (Rv0445c) and rskA (Rv0444c) from Mycobacterium orygis ( 6 , 36 ). In line with the previous report ( 36 ), we observed that this strain upregulated in vitro expression of MPT70 compared to wild-type (WT) H37Rv, while very little change was observed for the regulators of MPT70 transcription (SigK and RskA) ( Fig. 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…Having established associations between antigen expression and T cell quality, we investigated whether there was a causal relationship. For this, we utilized a newly described H37Rv strain, which has high in vitro expression of MPT70 due to a gene insert of the regulators sigK (Rv0445c) and rskA (Rv0444c) from M. orygis ( 36 ). Importantly, we observed that infection with this strain significantly increased the differentiation state of the MPT70-specific CD4 T cells and diminished their ability to enter the infected lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether T cell differentiation and vaccine protection is directly linked to in vivo antigen transcription, we utilised a recently engineered H37Rv strain (36) (herein called H37Rv::mpt70 high ) with significantly increased in vitro expression of MPT70 due to insertion of sigK (Rv0445c) and rskA (Rv0444c) from M. orygis (6, 36). In line with the previous report (36), we observed that this strain upregulated in vitro expression of MPT70 compared to wild type (WT) H37Rv, while very little changes were observed for the regulators of MPT70 transcription (SigK and RskA) (Figure 4a) . From this, we anticipated that the H37Rv::mpt70 high strain would have an increased early in vivo expression of MPT70.…”
Section: Resultsmentioning
confidence: 99%
“…Having established associations between antigen expression and T cell quality, we investigated whether there was a causal relationship. For this, we utilised a newly described H37Rv strain, which has high in vitro expression of MPT70 due to a gene insert of the regulators sigK (Rv0445c) and rskA (Rv0444c) from M. orygis (36). Infection with this strain significantly increased the differentiation state of the MPT70-specific CD4 T cells and diminished their ability to enter the infected lung tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation